2012
DOI: 10.1103/physrevlett.108.187601
|View full text |Cite
|
Sign up to set email alerts
|

Charge Order inLuFe2O4: An Unlikely Route to Ferroelectricity

Abstract: We present the refinement of the crystal structure of charge-ordered LuFe2O4, based on single-crystal x-ray diffraction data. The arrangement of the different Fe-valence states, determined with bond-valence-sum analysis, corresponds to a stacking of charged Fe bilayers, in contrast with the polar bilayers previously suggested. This arrangement is supported by an analysis of x-ray magnetic circular dichroism spectra, which also evidences a strong charge-spin coupling. The nonpolar bilayers are inconsistent with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
110
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(126 citation statements)
references
References 45 publications
14
110
1
1
Order By: Relevance
“…On the other hand, a very new work 7 reports on the occurrence of combined magnetoresistance and magnetocapacitance effects, i.e., the resistance and capacitance are suppressed by the magnetic field, and still supports the electronic ferroelectricity of LuFe 2 O 4 . From the structural point of view, recent singlecrystal x-ray-diffraction data agree with a structure of charged Fe nonpolar bilayers, 22 which is in contrast with the proposed CO with polar bilayers. 4 At this point, the only evidence for ferroelectricity in LuFe 2 O 4 is that provided by the pyroelectric current detection experiments.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…On the other hand, a very new work 7 reports on the occurrence of combined magnetoresistance and magnetocapacitance effects, i.e., the resistance and capacitance are suppressed by the magnetic field, and still supports the electronic ferroelectricity of LuFe 2 O 4 . From the structural point of view, recent singlecrystal x-ray-diffraction data agree with a structure of charged Fe nonpolar bilayers, 22 which is in contrast with the proposed CO with polar bilayers. 4 At this point, the only evidence for ferroelectricity in LuFe 2 O 4 is that provided by the pyroelectric current detection experiments.…”
Section: Introductionmentioning
confidence: 53%
“…The strong magnetic anisotropy with an easy magnetic axis parallel to the c axis, the ZFC-FC magnetic irreversibility in both geometries, and the sharp magnetic transition below 240 K are in accordance with previous reports in the literature. 11,[27][28][29] Electrical dc resistivity measurements were made on sintered polycrystalline bar-shaped samples (ρ pol ) with a size of 1 × 2 × 6 mm 3 and on single-crystal bar-shaped samples of a size of 0.5 × 0.6 × 1 mm 3 and 0.5 × 1 × 4 mm 3 with the electric field parallel (ρ c ) and perpendicular (ρ ab ) to the hexagonal c axis. The conventional four-probe configuration was used and electrodes were made using silver paint.…”
Section: Methodsmentioning
confidence: 99%
“…In our description, the charge at the iron site fluctuates above T CO , giving rise to a dynamical disproportion that is also followed by the local geometrical structure, and it is frozen at the iron sites below T CO . The only question that remains open is whether the charge distribution is bimodal or multimodal, taking into account that the low-temperature phase of LuFe 2 O 4 has the C/2m monoclinic symmetry with four distinct iron sites, which suggests four different charged iron atoms [27].…”
Section: Discussionmentioning
confidence: 99%
“…Although the occurrence of ferroelectricity can be discarded in LuFe 2 O 4 , the structural phase transition at T CO 320 K is still considered to originate from Fe 3+ /Fe 2+ CO. Resonant x-ray scattering (RXS) experiments at the Fe K-edge of the principal observed superstructure (1/3, 1/3, half-integer) reflections seem to support this assumption, but the analysis performed by either Ikeda et al [7] or Mulders et al [40] are merely qualitative, using a generic structure factor without considering any charge order sequence. Other authors have shown that the CO involves charged, rather than polar, bilayers with four different iron valences, but with values that are still grouped in a bimodal distribution of two different iron atoms, referred as Fe 3+ -and Fe 2+ -like [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation